KEMAMPUAN SISWA DALAM PENGGUNAAN HURUF KAPITAL DAN TANDA BACA PADA PENULISAN KARANGAN DESKRIPSI - Sri Mulyati, - (2022)
Writing skills are skills that must be mastered by students, which are useful for conveying messages or ideas through written media. Written grammar has rules in the form of General Guidelines for Indonesian Spelling (PUEBI). However, in the field there are still many students who do not understand these rules. As a result, students often make mistakes in writing, including errors in the use of capital letters and punctuation errors. The ability to use capital letters and punctuation marks can be seen from the results of student descriptions. The purpose of this study was to determine the students' ability to use capital letters and punctuation in descriptive essays. This research was carried out in the 2021/2022 academic year at SD Negeri 2 Paas, Pameungpeuk District, Garut Regency. This type of research is descriptive using a survey method involving the research subjects, namely 27 fifth grade students. The instrument in this research is a test to make descriptive reading texts. The results showed that the students' ability to determine capital letters and punctuation in descriptive essays was in the good category with an average score of 61. This study provides a view of the importance of analyzing students' abilities in using capital letters and punctuation in reviewing their development so that the writing made by students can meet the criteria of Indonesian grammar rules properly and correctly.